Ensuring Local Security: Cooperation of Municipal Wardens with other Entities - Miha, Dvojmoč (Magyar Rendészet, 2025)
The provision of security in local communities is the responsibility of various entities that have certain powers in the field of security provision. The primary task of municipalities is to take care of public safety and order, as well as the organisation of the municipality wardens. These have recently become a very important entity and factor in ensuring security in local communities. However, since security in the local community is a very broad category, several entities are needed to ensure it, as it is not fully covered by the responsibilities of municipal wardens. For this reason, it is important that security entities cooperate and connect with each other and thus effectively address security issues. These entities include, among others, the police, firefighters, rescue services, civil protection, inspectorates and the like. In the paper, research is carried out on the cooperation of municipal wardens with other entities that take care of security in the local community. The respondents answered various questions related to municipal wardens, their cooperation with other security entities in various fields, and also what obstacles they encounter in their cooperation. It highlights the advantages of effective cooperation and highlights the key challenges facing the modern security environment.